Chondromyxoid Fibroma of the Anterior Skull Base Invading the Orbit in a Pediatric Patient: Case Report and Review of the Literature - Khalatbari, Mahmoud Reza; Hamidi, Mehrdokht; Moharamzad, Yashar (Neuropediatrics, 2012)
Chondromyxoid fibroma (CMF) is a rare bone tumor of cartilaginous derivation representing less than 1% of all benign bone neoplasms. It is a slow-growing, locally destructive tumor that usually affects the metaphyseal region of long bones of patients in their second or third decade of life. Involvement of the skull base and orbit is extremely rare. We present the first case of histopathology-proven CMF originating in the greater sphenoid wing and extending into the orbit in a 14-year-old boy. He complained of pain and swelling of his left lateral orbit for 4 months and had 3-mm nonaxial proptosis. Magnetic resonance imaging of the orbit revealed a well-defined lesion in the lateral wall of the left orbit, hypointense on T1-weighted images, and heterogenous hyperintense on T2-weighted images and enhanced after contrast media injection. Through a left semicoronal skin incision, the mass was removed totally and the lateral orbital wall was reconstructed. The clinical manifestations, imaging findings, and surgical treatment of the lesion are discussed with a review of the literature.
Keywords: chondromyxoid fibroma; skull base; orbit